1986
DOI: 10.1111/j.1365-246x.1986.tb04362.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave polarizations in the Peter the First Range indicating crack-induced anisotropy in a thrust-fault regime

Abstract: Three-component seismograms of small local earthquakes recorded in the Peter the First Range of mountains near Garm, Tadzhikistan SSR, display shear-wave splitting similar to that previously observed near the North Anatolian Fault in Turkey. The Peter the First Range is in a region of compressional tectonics, whereas the North Anatolian Fault is a comparatively simple strike-slip fault. Detailed analysis of the Turkish records suggests that the splitting is diagnostic of crack-induced anisotropy caused by vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 7 publications
3
27
0
Order By: Relevance
“…The general match of APE-modelling in Table 2 is, at least, consistent with observations over an enormous range of frequencies (from MHz in the laboratory to kHz-5 Hz in the field (Holmes et al, 1993;Crampin et al, 1986b; respectively)), and dimensions from wavelengths of a few millimetres in the laboratory to 80 cm-hundreds of kilometres in the field (Holmes et al, 1993;Heffer and Bevan, 1990;respectively). The list is rapidly increasing (note the number of recent publication dates in the listed references).…”
Section: Ape-modellingsupporting
confidence: 61%
“…The general match of APE-modelling in Table 2 is, at least, consistent with observations over an enormous range of frequencies (from MHz in the laboratory to kHz-5 Hz in the field (Holmes et al, 1993;Crampin et al, 1986b; respectively)), and dimensions from wavelengths of a few millimetres in the laboratory to 80 cm-hundreds of kilometres in the field (Holmes et al, 1993;Heffer and Bevan, 1990;respectively). The list is rapidly increasing (note the number of recent publication dates in the listed references).…”
Section: Ape-modellingsupporting
confidence: 61%
“…To avoid potential ambiguity, it is worthwhile to mention that in an anisotropic medium, aligned fast shear-wave polarization orientations are independent of the initial polarization of the shearwave at the source and are mainly caused by the medium's anisotropy (e.g. Crampin et al, 1986;Peacock et al, 1988;Crampin and Lovell, 1991).…”
Section: Inversion Methods and Resultsmentioning
confidence: 99%
“…The phenomenon is very similar to optical birefringence, whereby light transmitted through an anisotropic crystal undergoes analogous splitting and polarization parallel and perpendicular to the alignment of atoms in the crystal lattice. In the seismic case, the polarization direction of the fast split shear wave parallels the strike of the predominant cracks regardless of its initial polarization at the source (Crampin et al, 1986;Peacock et al, 1988). The differential time delay between the arrival of the fast and the slow shear waves (typically a few tens of milliseconds) is proportional to crack density, or number of cracks per unit volume within the rock body traversed by the seismic wave (Hudson, 1981;Crampin, 1987;Crampin and Lovell, 1991).…”
Section: Shear-wave Splittingmentioning
confidence: 99%
“…Wave polarisation and the delay between the two phases vary with azimuth, allowing the symmetry of the anisotropy to be identified. Crampin et al (1986) suggested that stress aligned fluid-filled cracks (with dimensions of less than one wavelength of the S -wave) are the cause of shear wave splitting . Both Crampin et al (1986) and Peacock et al (1988) report observations of temporal variation in shear-wave splitting, over periods of years, interpreted as due to changes in the microcrack population induced by stress change.…”
Section: Classification Of Measurement Techniquesmentioning
confidence: 98%